Modeling of unsteady heat transfer processes in combined coatings (Международный научный журнал «Инженер», 2026)
Modeling of unsteady heat transfer processes in combined coatings is an important task for the development of efficient technologies and materials used in various industries such as mechanical engineering, energy, construction and others. Combined coatings are multi-layered structures that provide protection from external influences, improving the performance of materials.